The predictive roles of obesity and serum vitamin D levels in body response to hepatitis B vaccine - hasanzadeh, Aylar; Moludi, Jalal; farsad naemi, Alireza; Alizadeh, Mohammad; Kheirouri, Sorayya (Progress in Nutrition, 2018)
Background: Hepatitis B vaccination is the most successful way to prevent the virus infection. Serum concentration of vitamin D has recently been proposed as a novel predictor of response to antiviral treatment in chronic hepatitis infection.  Objectives: This study aimed to verify whether the relationship between obesity, serum levels of vitamin D and TNF- α, after immunization with hepatitis B vaccine, plays a role in predicting the rates of antibody titer. Methods: The present study included 45 men and women aged 20 to 50 years old who were assigned in following two groups based on BMI: (A) normal weight and (B) overweight or obese subjects. Both groups received Hepatitis B vaccine in three dozes at; 0, 1, 2 month intervals. Then, Linear Regression analysis was used to evaluate the relationship between serum vitamin D levels and antibody titers. Results: A total number of 45 patients (30 males and 15 females) with a mean age of 35.765±6.63 years were studied. There was a significant difference shown in the mean of vitamin D (P= 0.013) and TNF-α (P= 0.469) between the two groups. Linear regression analysis revealed a significantly lower HBSAg among only female participants with overweight or obesity (P= 0.015). Serum vitamin D level was a main predictor of body response to hepatitis B vaccine and 1 ng/ml increase in serum vitamin D level was associated with a rise of 8.77 IU/mL in HBSAg levels. Conclusions: In our study, after adjusting of other factors, serum vitamin D level was a main predictor of body response to hepatitis B vaccine. Moreover, our study revealed an association between vitamin D deficiency and poor body response to vaccination in obese patients.